2021
DOI: 10.1021/acs.est.0c05231
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Model for Understanding N2O Emissions from Wastewater Treatment Plants: A Deep Learning Approach

Abstract: This study aims to demonstrate the application of deep learning to describe quantitatively longterm full-scale data observed from wastewater treatment plants (WWTPs) from the perspectives of process modeling, process analysis, and forecasting modeling. Approximately 750,000 measurements incorporating influent flowrate, air flowrate, temperature, ammonium, nitrate, dissolved oxygen, and nitrous oxide (N2O) during more than one year of Avedøre WWTP located in Denmark are utilized to develop deep neural network (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…A deep learning method such as RNN may play a role in this respect. The latest study used LSTM to process modeling and forecasting of N 2 O emission from WWTPs, and the obtained model showed a better performance in comparison to the previously reported DNN-based model ( R 2 > 0.94). The forecast of municipal solid waste (MSW) generation is also a time series analysis problem with high temporal variation.…”
Section: Selelcted Applicatons Of Machine Learning In Environmental P...mentioning
confidence: 93%
“…A deep learning method such as RNN may play a role in this respect. The latest study used LSTM to process modeling and forecasting of N 2 O emission from WWTPs, and the obtained model showed a better performance in comparison to the previously reported DNN-based model ( R 2 > 0.94). The forecast of municipal solid waste (MSW) generation is also a time series analysis problem with high temporal variation.…”
Section: Selelcted Applicatons Of Machine Learning In Environmental P...mentioning
confidence: 93%
“…In this study, we divide data preprocessing methods into two parts: moving average and normalization. The moving average is a data smoothing method that is capable of smoothing high-frequency noise, and making the pattern more visible than original is required to ensure the stability of model performance [ 30 ]. The smoothing formula is shown in Equation (1) .…”
Section: Methodsmentioning
confidence: 99%
“…Instead of using sensitivity analysis, we selected the design parameters by ranking the results of simulations made using all possible permutations of three design parameters. In the context of the forecast modeling of N 2 O concentrations in wastewater treatment plants, Hwangbo et al [52] observed that an LSTM model outperformed a DNN model in terms of forecast prediction accuracy. They noted that the LSTM-based forecasting modeling depends on the response data, whereas all sensor data can be used as predictors in DNN models.…”
Section: Comparison To Existing Methodsmentioning
confidence: 99%